HUBUNGAN PERAN KELUARGA DENGAN UPAYA PERAWATAN HIPERTENSI PADA LANSIA PENDERITA HIPERTENSI DI KELURAHAN PADANGSARAI WILAYAH KERJA PUSKESMAS AIR DINGIN PADANG TAHUN 2017 - DALINA GUSTI - (Menara Ilmu, 2018)
WHO (2012) says hypertension can trigger a stroke that causes death to 51% andhypertension leads to coronary heart disease that causes deaths of up to 45%. Riskesdas data in2013 in Indonesia shows the prevalence of hypertension in elderly people, 55-64 years oldabout 45.9%, 65-74 years old about 57.6%, and 75 years oldand above about 63.8%. Datafrom Puskesmas Anak Air showed the number of hypertensive disease to-2 that is 1.002 cases.The purpose of this study is to determine the relationship of family roles with hypertensioncare efforts.Type of cross-sectional analytic design study, the study was conducted from March 25to April 22, 2017, the population is all elderly in Kelurahan PadangSarai Working AreaPuskesmas Anak Air Padang, the number of samples 54 elderly. Data was collected throughinterviews and questionnaires given to the respondents, the data were analyzed with Univariateand Bivariat.The results obtained from 54 respondents 28 respondents (53.8%) who have a positiverole, 30 respondents (57.7%) have high care for the elderly. There is a relationship betweenfamily role with hypertension care in elderly with p = 0.000 (p ≤ 0.005).Based on the research results obtained have a positive role and more than half ofrespondents have high care about hypertension in elderly. It is expected that the puskesmas tomaintain and increase education and health education to the family, especially abouthypertension treatment in elderly.Key Word: Family Role, Hypertension Treatment Effort